Pengaruh Tingkat Pemahaman Etika Perpajakan dan Tingkat Pengetahuan Perpajakan Terhadap Praktik Tax Avoidance Sebagai Strategi Perencanaan Pajak Perusahaan - Aliyya Miya Savitri; I G.A. Desy Arlita (Economic Reviews Journal, 2026)
This study aims to examine the effect of tax ethics understanding and tax knowledge on tax avoidance practices as a corporate tax planning strategy, based on the Theory of Planned Behavior. This research employs a quantitative approach using purposive sampling to collect data from 100 companies registered as corporate taxpayers and operating in Denpasar City through an online questionnaire. The data were analyzed using multiple linear regression analysis. The results show that, partially, tax ethics understanding has a positive and significant effect on tax avoidance practices, indicating that ethical awareness encourages companies to conduct tax planning in a more structured, legal, and controlled manner. Furthermore, tax knowledge also has a positive and significant effect on tax avoidance, suggesting that a better understanding of tax regulations and facilities enhances companies’ ability to manage their tax obligations efficiently. Simultaneously, tax ethics understanding and tax knowledge significantly explain variations in corporate tax avoidance practices. This study concludes that tax ethics and tax knowledge play an important role in shaping corporate tax planning behavior that balances legal compliance with moral considerations within the taxation system.